Escola, catequese e formação de professores: os missionários orionitas e a catolicização do antigo extremo norte de goiás por intermédio da educação, 1950-1960 / School, catechesis and teacher formation: the orionite missionaries and the catholicization of the old far Northern Goiás through education, 1950-1960 - Silva, Raylinn Barros da (Revista de História e Historiografia da Educação, 2020)
O objetivo deste estudo é refletir o processo de catolicização do antigo extremo norte de Goiás, por intermédio da educação, processo desencadeado pelos missionários católicos orionitas nas décadas de 1950 e 1960. Este estudo é resultado de uma pesquisa bibliográfica e as fontes analisadas são as obras de memória dos próprios missionários. A justificativa para este estudo é a necessidade de historicizar essas fontes, o que contribui para a compreensão de parte da história religiosa da região, atual norte do Tocantins. *** The aim of this study is to reflect the process of catholicization of the ancient far northern of Goiás, through education, a process triggered by the Orionite Catholic missionaries in the 1950s and 1960s. This study is the result of a literature search and the sources analyzed were pieces of memory of the own missionaries. The justification for this study is the need to historicize these sources, which contributes to the understanding of part of the religious history of the region, current northern Tocantins.